The Effectiveness of the Elsa Speak Application in Enhancing Students’ Pronunciation Ability at SMK Yadika Palu - Mila Revina; Muhammad Arid; Fadhilah Zamzam; Mocthar Marhum (Journal of General Education and Humanities, 2026)
This study was conducted to address the problem of low pronunciation ability among EFL students, particularly in producing accurate phonemes and applying correct word stress, which is caused by limited practice, low confidence, and lack of motivation. The objective of this study was to investigate the effectiveness of the ELSA Speak application in improving students’ pronunciation ability at SMK Yadika Palu. This study employed an applied quantitative research method using a quasi-experimental design involving an experimental group and a control group. The participants were 40 eleventh-grade students, equally divided into two groups. The experimental group received pronunciation instruction using the ELSA Speak application, while the control group received conventional pronunciation instruction. Data were obtained through pre-test and post-test assessments focusing on phoneme articulation and word stress and were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Mann–Whitney U test, and effect size calculation. The results showed that both groups had similar pre-test mean scores, indicating comparable initial pronunciation ability. However, the post-test results revealed that the experimental group achieved a significantly higher mean score than the control group. The Mann–Whitney U test indicated a statistically significant difference (p < 0.05) with a very large effect size, demonstrating that the ELSA Speak application had a strong positive effect on students’ pronunciation improvement. Therefore, this study concludes that ELSA Speak is an effective Mobile-Assisted Language Learning (MALL) tool for enhancing pronunciation instruction in vocational high school contexts.